Clinical and radiographic sequelae to primary teeth affected by dental trauma: a 9-year retrospective study - Vanessa Polina Pereira Costa; Marilia Leão Goettems; Elaine Zanchin Baldissera; Andréa Dâmaso Bertoldi; Dione Dias Torriani
Abstract This retrospective study aimed at determining the predicted risks of clinical and radiographic complications in primary teeth following traumatic dental injuries, according to injury type, severity and child's age. Data were collected from records of children treated at a Dental Trauma Center in Brazil for nine years. Records of 576 children were included; clinical sequelae were assessed in 774 teeth, and radiographic sequelae, in 566 teeth. A total of 408 teeth (52.7%) had clinical sequelae and 185 teeth (32.7%), radiographic sequelae. The type of injury with the highest number of clinical sequelae was the crown-root fracture (86.4%). Clinical sequelae increased with injury severity (p < 0.001), whereas radiographic sequelae did not (0.236). The predicted risk of color change was 29.0% (95%CI 19-41) for teeth with enamel fracture, and 26.0% (95%CI 14-40) for teeth with enamel dentin fracture as well as enamel dentin pulp fracture. Risk of periapical radiolucency was higher for teeth with enameldentinpulp fracture (61.1% 95%CI 35-82) and those with subluxation (15.8% 95%CI 10-22). Risk of premature loss was 27.3% (95%CI 13-45) for teeth with extrusive luxation, and 10.2% (95%CI 5-17) for those with intrusive luxation. The assessment of predicted risks of sequelae showed that teeth with hard tissue trauma tended to present color change, periapical radiolucency and premature loss, whereas teeth with supporting tissue trauma showed color change, abnormal position, premature loss and periapical radiolucency as the most common sequelae. Knowledge about the predicted risks of complications may help clinicians establish appropriate treatment plans.